2020
DOI: 10.1186/s40337-019-0276-9
|View full text |Cite
|
Sign up to set email alerts
|

Food related attention bias modification training for anorexia nervosa and its potential underpinning mechanisms

Abstract: Treatment outcomes in anorexia nervosa (AN) remain suboptimal, evidencing the need for better and more targeted treatments. Whilst the aetiology of AN is complex, cognitive processes such as attention bias (AB) have been proposed to contribute to maintaining food restriction behaviour. Attention bias modification raining (ABMT) has been investigated in other eating disorders (EDs) such as binge eating disorder (BED) as a means of modifying AB for food and of changing eating behaviour. Promising findings have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 21 publications
6
61
0
Order By: Relevance
“…In this study, one in three participants reported lower physical activity levels during lockdown. This significant prevalence of lower physical activity was also reported by a cross-sectional survey among Lebanese adults, whereby 41% reported no physical activity or exercise during lockdown [ 25 ]. In fact, staying home for a prolonged period of time may lead to more prevalent sedentary behavior such as excessive sitting/reclining, increased screen time activities (video games, TV watching, use of mobile devices) [ 26 ].…”
Section: Discussionsupporting
confidence: 69%
“…In this study, one in three participants reported lower physical activity levels during lockdown. This significant prevalence of lower physical activity was also reported by a cross-sectional survey among Lebanese adults, whereby 41% reported no physical activity or exercise during lockdown [ 25 ]. In fact, staying home for a prolonged period of time may lead to more prevalent sedentary behavior such as excessive sitting/reclining, increased screen time activities (video games, TV watching, use of mobile devices) [ 26 ].…”
Section: Discussionsupporting
confidence: 69%
“…A balance of risks should be considered as families are within the same “bubble” and pose limited additional risk, whereas the reduction in treatment effectiveness could be life threatening. Future research must aim to understand how best to adapt treatments, such as FBT, for virtual delivery to ensure that it is safe and effective [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include cognitive remediation approaches that focus on cultivating a flexible, big picture style of thinking [73], cognitive skills training for social avoidance [74], and go/no-go inhibition training [75], which may be of value for the binge-purge form of the illness. Food-related attention bias modification training is also being investigated as an add-on intervention for AN, following directions from anxiety disorder research [76,77].…”
Section: Behavioural Consequences Of Anorexia Nervosamentioning
confidence: 99%